The Relationship between Stress Level with Menstrual Cycle Disorders among Female Adolescents - Cut Nabilla Naifa Syahira Wibawa; Yaslinda Yaunin; Fika Tri Anggraini (Indonesian Journal of Global Health Research, 2026)
Adolescent represents a critical transitional stage characterized by biological, psychological, and social changes, including the onset of menstruation as an indicator of reproductive maturity. Menstrual cycle disorders are common among adolescents and may be influenced by several stress. This study aimed to examine the association between stress levels with menstrual cycle disorders among female adolescents. A quantitative analytic observational study with a cross-sectional design was conducted among 278 female students selected through proportionate stratified random sampling. Data were collected using a standardized structured questionnaires, interviews, and anthropometric measurements, and analyzed using the Chi-square test. The results showed that most respondents were 16 years old (53.2%), and menarche predominantly occurring at the age of 12 years old (43.2%). The majority had mild stress levels. Bivariate analysis revealed significant associations between stress level (p = 0.000 ; p = 0.005). The conclusion of the study is that stress levels the factors most closely related to menstrual cycle disorders in adolescent girls.